Opportunities and Challenges of Offline Tutoring in South Sulawesi - Jusman Jusman; Romansyah Sahabuddin; Muhammad Irfan; Rahmawati Patta; Andi Yuyun (Departement of Mathematics Education, 2024)
This study aims to identify and analyze the opportunities and challenges faced by offline tutoring in South Sulawesi, focusing on the impact of education policy, student behavior, and competition between offline and online tutoring. Through a mixed approach utilizing both qualitative and quantitative data, this study conducted interviews with tutoring managers, a survey of students, and statistical analysis of student participation and learning outcomes. The findings show that while offline tutoring has advantages in building better social interaction and motivation to learn, challenges such as the shift towards online tutoring platforms and restrictions due to the COVID-19 pandemic are significant obstacles. The significance of these findings suggests the importance of adapting teaching methods and developing effective marketing strategies to attract students back to offline tutoring. In addition, the implications of this study can contribute to the development of educational policies that are more responsive to learners' needs and improve the quality of tutoring. By understanding these dynamics, education stakeholders, including tutoring managers and the government, can take more strategic steps to strengthen the presence and relevance of offline tutoring in the current education ecosystem.